PHYSICOCHEMICAL AND MICROBIAL ACTIVITY OF WASTE WATER OBTAINED FROM KWANAR-ARE DAM, RIMI LOCAL GOVERNMENT AREA OF KATSINA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
This study investigated the contamination level of wastewater in Kwanar-Are Dam. Samples were collected during wet and dry seasons. Determination of both Faecal coliform and the Escherichia coli counts were performed using standard membrane filtration and multiple tube techniques, while parameters such as pH, electrical conductivity, Biochemical Oxygen Demand, nitrate, sulphate, crbonate, bicarbonate and chloride were evaluated using standard methods of analysis. The bacterial isolates recovered from the water samples were Escherichia coli and Entrobacter aerogenes. Prevalence showed that both Escherichia coli and Entrobacter aerogenes isolated from 5 different samples labeled as A, B C, D and E. Escherichia coli was recovered in samples A, B and C while Entrobacter aerogenes was found in sample D and E. The results obtained for dry season ranged between 33 cfu/100ml to 13 cfu/100mls, while that of wet season dropped from 5.5 cfu/100mls to 2.0cfu/100mls. Similarly, the results for pH (7.19 and 8.68) and nitrate (9.33mg/l and 7.78 mg/l) were above WHO limits. This is an indication that the water samples were contaminated, especially with faecal materials and therefore unsafe for drinking and other domestic activities. However, the results for electrical conductivity (14.42-15.79ÂµS/cm), chloride (41.18 -51.12mg/l), sulphates (48.01-58.40mg/l) and BOD (3.3-1.7mg/l) were within WHO limits. Therefore, routine monitoring and public enlightenment should be enforced to ensure adherence to drinking water standard and other sources of portable water for drinking and domestic purposes should be provided to the community. The gross pollution of the dam exposes the local people who depend on it
Keywords: Bacterial analysis, waste water, feacal coliform, E. coli, E.aerogenes